Relationship of obesity to mortality in 47, 399 patients from nationwide LIPIDOGRAM 2004–2015 cohort studies. (3rd October 2022) - Osadnik, T; Banach, M; Gierlotka, M; Nalewajko, K; Nowak, D; Zak, Z; Skowron, L; Lewandowski, P; Jozwiak, J
Abstract: Background: Evidence suggests that obesity may be associated with lower mortality rates in various cohorts of patients (obesity paradox). One possible explanation is unmeasured confounding factors induced by selection bias (collider stratification bias). Therefore, data from large cohorts with few exclusion criteria are of value as they may minimize this effect. Purpose: To assess the association between two obesity measures body mass index (BMI; kg/m 2 ) and waist circumference (WC; cm) with mortality in nationwide cohort of 47, 399 patients. Methods: Lipidogram studies were carried out in Poland in 2004, 2006 and 2015 in the population representative for patients in primary care setting. The median follow up was 5570 days. Patients were recruited in all 16 administrative regions in Poland and physicians were proportionally to the number of inhabitants in a given administrative region. Each patient was given a questionnaire on chronic diseases, treatment and lifestyle. Questionnaire was administered by physician. Association between BMI, WC and mortality was assessed by multivariate Cox regression and spline regression models. Weight status was classified as underweight (BMI <18.5), normal weight (BMI 18.5–24.9), overweight (BMI 25–29.9), class I obesity (BMI 30–34.9), class II obesity BMI (35–39.9), and class III obesity BMI (>40). Results: The prevalence of hypertension, dyslipidemia, diabetes and coronary artery disease, showed a graded association with BMI, whilst smoking was most frequent in underweight patients. Correlation between BMI and WC was 0.748. As compared to normal weight patients' class III obese patients had highest mortality (HR 1.91; 95% CI: 1.650–2.202), following by class II obesity (HR 1.47, 95% CI: 1.33–1.62) and underweight patients (HR 1.47; 95% CI 1.1–1.8). Overweight patients had also slightly increased risk of dying as compared to normal weight patients (HR 1.12; 95% CI: 1.05–1.19). Similar U-shaped curve was observed for waist circumference. After adjustment for age, sex, smoking, diabetes, hypertension and LDL cholesterol highest mortality was observed for underweight patients (HR 1.88; 95% CI: 1.44–2.45), following by class III obesity (HR–1.51; 95% CI 1.31–1.75). Class I obesity and being overweight was associated with lower risk (HR 0.88; 95% CI: 0.82–0.94 and HR 0.86; 95% CI: 0.81–0.92, respectively). Conclusions: No evidence of obesity paradox was present in unadjusted analysis. Lower mortality was observed in overweight and class I obese patients only after adjustment for risk factors and diseases typically associated with obesity. Results of multivariate analysis indicate that diseases that develop in obese patients are significantly associated with mortality more than obesity itself. Confounding may be responsible for discussed obesity paradox in literature therefore preventive measures to maintain BMI within normal range and prevent development of its complications should not be abolished. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The present study was funded by an unrestricted educational grant from Valeant. As a supporter of the study, Valeant played no role in the study design, data analysis, data interpretation, or writing of the report. The present study was also supported by Silesian Analytical Laboratories (SLA, Katowice, Poland).